Clinical and Socio-Demographic Profiles of Patients Seen with Rheumatic Heart Disease in a Cardiac Clinic of a Tertiary Hospital in Ghana - Owusu IK; Acheamfour-Akowuah E; Wiafe YA (Research Reports in Clinical Cardiology, 2022)
Isaac Kofi Owusu,1,2 Emmanuel Acheamfour-Akowuah,1,2 Yaw Amo Wiafe3 1Department of Medicine, School of Medicine and Dentistry, College of Health Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana; 2Directorate of Medicine, Komfo Anokye Teaching Hospital, Kumasi, Ghana; 3Department of Medical Diagnostics, College of Health Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, GhanaCorrespondence: Isaac Kofi Owusu, Email ikeowusu@yahoo.comBackground: Rheumatic heart disease (RHD) is mainly among populations in low-to-middle income nations. The burden of this disease on communities and even hospital settings is little understood. This study aimed at analysing the clinical and socio-demographic features of RHD patients in our adult outpatient cardiac department over a 3-year period.Methods: The study was conducted at the Komfo Anokye Teaching Hospital’s Adult Cardiac Clinic in Kumasi, Ghana. Medical records of patients seen at the adult cardiac clinic between 2016 and 2019 with the diagnosis of rheumatic heart disease were examined. The data were captured using EPI-DATA (version 3.1). Stata 14 was used in analysing the mean (standard deviation) and median of continuous variables (inter-quartile range). The frequency and percentages were used to describe categorical data. The Chi-square test was used to establish the statistical significance of a relationship, with a p-value of less than 0.05.Results: A total of 140 RHD cases were included in the study. The average age of patients was 39.7 years. Majority of the participants (82.9%) were from rural areas. Palpitation was the commonest symptom (54.29%), followed by chest pains (36.43%), dyspnoea (25.00%), and dizziness (24.29%). Over seventy-seven percent (77.14%) of the patients had moderate-to-severe rheumatic heart disease. The commonest valvular lesion was isolated mitral regurgitation (56.43%), followed by pure aortic regurgitation (30.71%), and isolated tricuspid regurgitation (12.14%).Conclusion: RHD occurred more commonly in the third decade of life. Rural participants, who are primarily females, were the most affected. Efforts to reduce prevalence rates should be stepped up.Keywords: rheumatic heart disease, acute rheumatic fever, heart failure, mitral regurgitation, echocardiography